Bilateral ovarian leiomyoma treated by standing laparoscopic ovariectomy. (October 2015) - Daniel, A.; McCue, P.; Ferris, R.; Miller, C.; Leise, B.
Summary An 11‐year‐old Warmblood mare presented to a referral facility due to behavioural problems. A hormonal profile performed prior to referral included increased systemic concentrations of testosterone and progesterone but a low concentration of inhibin. Transrectal ultrasound revealed ovaries consistent with a normal cycling mare. At the request of the owner, standing bilateral laparoscopic ovariectomy was performed without complication. Both ovaries were submitted for histopathological examination which revealed bilateral ovarian leiomyoma.